2007
DOI: 10.1128/iai.00324-07
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of an Iron-Regulated Hemin-Binding Protein, HbpA, fromLeptospira interrogansSerovar Lai

Abstract: In an earlier study, based on the ferric enterobactin receptor FepA of Escherichia coli, we identified and modeled a TonB-dependent outer membrane receptor protein (LB191) from the genome of Leptospira interrogans serovar Lai. Based on in silico analysis, we hypothesized that this protein was an iron-dependent hemin-binding protein. In this study, we provide experimental evidence to prove that this protein, termed HbpA (hemin-binding protein A), is indeed an iron-regulated hemin-binding protein. We cloned and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 36 publications
1
42
1
Order By: Relevance
“…HbpA was first reported as an iron-regulated, haeminbinding protein in serovar Lai (Sritharan et al, 2005;Asuthkar et al, 2007). Its absence from non-pathogenic Leptospira species and the in vivo expression of the protein, coupled to its usefulness in screening of clinical isolates by PCR (Sridhar et al, 2008) and ELISA (Sivakolundu et al, 2011), led us to extend its usefulness to the diagnosis of leptospiral uveitis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…HbpA was first reported as an iron-regulated, haeminbinding protein in serovar Lai (Sritharan et al, 2005;Asuthkar et al, 2007). Its absence from non-pathogenic Leptospira species and the in vivo expression of the protein, coupled to its usefulness in screening of clinical isolates by PCR (Sridhar et al, 2008) and ELISA (Sivakolundu et al, 2011), led us to extend its usefulness to the diagnosis of leptospiral uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…Its absence from non-pathogenic Leptospira species and the in vivo expression of the protein, coupled to its usefulness in screening of clinical isolates by PCR (Sridhar et al, 2008) and ELISA (Sivakolundu et al, 2011), led us to extend its usefulness to the diagnosis of leptospiral uveitis. Recombinant HbpA was prepared as described previously (Asuthkar et al, 2007) and we showed that there are no epitopes in the protein that are shared with other bacterial proteins. There was low crossreactivity with other TonB-dependent proteins within the same organism, as reflected by the low reactivity of the leptospiral extract of L. interrogans serovar Manilae grown under high-iron conditions; a threefold increase was seen in extracts of low-iron-grown organisms as a result of increased expression of HbpA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations